Frank Stella - Stella, Frank; Campbell, Andrianna; Nesin, Kate; Blalock, Lucas; Richardson, Terry, 1965- (New york, 2017)
Initially influenced by the work of the abstract expressionists, Frank Stella subsequently rejected the movement in favour of more radical forms. In 1960, Stella presented his first series of aluminium paintings at Leo Castelli, causing the first upset in a long history of experiments that saw him tackling minimalism, post-painterly abstraction, and public art. This book examines Stella's life and career in the context of the contemporary art world, featuring works from his recent blockbuster museum exhibitions as well as landmark works from throughout his career. The book includes a complete visual reportage of Stella's studio in upstate New York, shot by Terry Richardson.
Interview: Andrianna Campbell in conversation with Frank Stella -- Survey: So what are you made of? And where do you come from? (A speculative survey of Frank Stella's practice) / Kate Nesin -- Focus: Scarlatti K / Lucas Blalock, -- Studio visit / Terry Richardson -- Artist's writings -- Lecture in Havanna, 2016 -- Chronology.
Includes bibliographical references (page 157).
Keywords: Stella, Frank -- Catalogs-kataloge; Stella, Frank -- Interviews-intervista -- Artet boterore; Stella, Frank. -- Arti vizual; Arti modern; Artiste amerikane; 1900-2099; Painting -- United States-Shtetet e bashkuara -- 20th century-shekulli i 20-te; Painting -- United States -- 21st century-shekulli i 21-te; Sculpture -- United States -- 20th century; Sculpture -- United States -- 21st century; Painting; Sculpture; United States; Artiste amerikane-Frenk Stela-piktura-skulptura-arti abstrakt-arti bashkekohor; abstraktsioni gjeometrik-iluzionizmi abstrakt-teknika-metoda-mjetet-materialet; Catalogs; Interviews